A comparison of two laboratory methods to test dental unit waterline water quality - Porteous, Nuala (2013)
The performance of two APHA standard laboratory methods, the R2A spread plate and the SimPlate™ for heterotrophic plate count (HPC), for quantifying heterotrophic microorganisms in dental waterline samples was evaluated. Microbial counts were underestimated on SimPlate™ compared with R2A and the results indicated a poor correlation between the two methods.